CiênciaBrasil - The Brazilian Portal of Science and Technology - Laender, Alberto H. F.; Moro, Mirella M.; Silva, Altigran S.; Davis Jr., Clodoveu A.; Gonçalves, Marcos André; Galante, Renata; Silva, Allan J. C.; Bigonha, Carolina A. S.; Dalip, Daniel Hasan; Barbosa, Eduardo M.; Borges, Eduardo N.; Cortez, Eli; et al. (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2011)
Research social networks are a potentially useful resource for studying science and technology indicators from specific communities (e.g., a country). However, building and analyzing such networks beget challenges beyond those from regular social networks, since data about actors and their relationships are usually dispersed across various sources. In this paper, we present a research social network built from an individual perspective by gathering data from a Brazilian curricula vitae repository. We describe its architecture and the solutions adopted for data collection, extraction and deduplication, and for materializing and visualizing the network.